Elemental abundance analyses with DAO spectrograms. XXXIX. The am stars 2 UMa and 15 Vul - Çay, İpek; Teker Yelkenci, Ayşegül; Adelman, Saul J. (Iop Publishing Ltd, Temple Circus, Temple Way, Bristol Bs1 6Be, England, 2016)
We derived the elemental abundances of the metallic-line stars 2 UMa (=HR 3354; spectral type A2m) and 15 Vul (=HR 7653; spectral type A4 III), using high-dispersion, high signal-to-noise ratio (>= 200) optical region spectrograms obtained with CCD detectors at the long Coude camera of the 1.22 m telescope of the Dominion Astrophysical Observatory (DAO) and Kurucz's ATLAS9 and WIDTH9 programs. The star 2 UMa has not been the subject of a modern detailed elemental abundances analysis. It is relatively sharp-lined and sufficiently hot (T-eff = 8050 K) that the continuum placement is not a major problem in the optical region. Comparison of the results of this new study of 15 Vul with the last complete study shows a 0.15 dex mean increase in the derived abundances and a reduction in the standard deviations of the mean values. The abundance anomalies of 2 UMa are usually larger than those of 15 Vul. The greater spectral coverage of 15 Vul compared with 2 UMa results in a larger number of abundances being derived. The abundances of 2 UMa are typical for those of classical Am stars that have similar effective temperatures and surface gravities. 15 Vul, characterized by a similar effective temperature and smaller surface gravity, is a more evolved star.
Keywords: Stars; Abundances; Stars; Chemically Peculiar